On the abortifacient effects of the estroprogestin pill and other "contraceptives" - Di Pietro, Maria Luisa; Minacori, Roberta (Medicina e Morale, 1996)
In order to control fertility, various contraceptive techiques are used today and in most cases they prevent conception temporarily. Apart from so-called contraceptives other techniques are also used and although these are marketed as contraceptives, in reality they do not act by preventing the beginning of a pregnancy but by preventing a pregnancy that has already begun from evolving normally. Therefore the latter techniques are abortifacient. The article studies the mechanism of action and the capacity of abortion of some "contraceptives" like the estroprogestin pill (monophasic, biphasic pills, pills with a mainly androgenic action), of the so-called "interceptives" (minipill; depot progestins like the injectable preparations, skin grafts and vaginal rings; the coil or IUD; the one defined as "post-coital or emergency contraception") and the so-called "contragestatives" (RU486, prostaglandins, abortifacient vaccines). The results of the study show that the current research in the field of birth control is mainly directed towards products with an abortifacient action and that there is an attempt, also by the international literature, to make the public opinion accept them, by disguising them or mystifying the "abortion" aspect. In a situation like this semantic and scientific reality is more necessary than over, otherwise people can be subject to manipulation while they think they are free.